Splitting scheme for gyro-kinetic equations with Semi-Lagrangian and Arakawa substeps - Bell Dominik; Pinto Martin Campos; Kumozec Davor; Schnack Frederik; Bourne Emily; Sonnendrücker Eric (ESAIM: Proceedings and Surveys)
The gyro-kinetic model is an approximation of the Vlasov-Maxwell system in a strongly magnetized magnetic field. We propose a new algorithm for solving it combining the Semi-Lagrangian (SL) method and the Arakawa (AKW) scheme with a time-integrator. Both methods are successfully used in practice for different kinds of applications, in our case, we combine them by first decomposing the problem into a fast (parallel) and a slow (perpendicular) dynamical system. The SL approach and the AKW scheme will be used to solve respectively the fast and the slow subsystems. Compared to the scheme in [1], where the entire model is solved using only the SL method, our goal is to replace the method used in the slow subsystem by the AKW scheme, in order to improve the conservation of the physical constants.